Analysis of Resistance to Florfenicol and the Related Mechanism of Dissemination in Different Animal-Derived Bacteria - Li, Peizhen; Zhu, Tingyuan; Zhou, Danying; Lu, Wei; Liu, Hongmao; Sun, Zhewei; Ying, Jun; Lu, Junwan; Lin, Xi; Li, Kewei; Ying, Jianchao; Bao, Qiyu; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Bacterial resistance to the antibiotics has become an important concern for public health. This study was aimed to investigate the characteristics and distribution of the florfenicol-related resistance genes in bacteria isolated from 4 farms. A total of 106 florfenicol-resistant Gram-negative bacilli were examined for florfenicol-related resistance genes and the positive isolates were further characterized. Antimicrobial sensitivity results showed that most of them (100, 94.33%) belonged to multidrug resistance Enterobacteriaceae. About 91.51% of the strains carried floR gene, 4.72% carried cfr gene. According to the Pulsed-field gel electrophoresis (PFGE) results, 34 E. coli were subdivided into 22 profiles, the Genetic Similarity coefficient ranged from 80.3% to 98.0%. Multilocus sequence typing (MLST) results revealed 17 sequence types (STs), with ST10 being the most prevalent. The genome sequencing result showed that Proteus vulgaris G32 genome consists of a 4.06-Mb chromosome, a 177,911 bp plasmid (pG32-177) and a 51,686 bp plasmid (pG32-51). A floR located in a drug resistant region on the chromosome of P. vulgaris G32 was with IS91 family transposase, and the other floR gene on the plasmid pG32-177 was with an ISCR2 insertion sequence. The cfr gene was located on the pG32-51 flanked by IS26 element and TnpA26. This study suggested that the mobile genetic elements played an important role in the resistance genes replication and the horizontal resistance gene transfer.